Analyzing procurement route selection for electric power plants projects using SMART - Marzouk, Mohamed; Elmesteckawi, Lobna (Journal of Civil Engineering and Management, 2018)
The decision of selecting the appropriate procurement/delivery system for large investment construction projects is a critical and challenging task for clients, and therefore a significant factor for the project’s success. Complex projects as electric power plants can involve managing multiple contracts or subcontracts simultaneously or in sequence. The aim of this paper is to develop, and analyze a decision support tool to select the most efficient procurement/delivery system for multiple contracts Combined Cycle Power Plants (CCPP) constructed in Egypt and funded by the publicsector. This process involved the identification of various procurement routes, followed by the utilization of quantitative values developed in accordance with the requirements of the multi-criteria decision analysis technique known as simple multi-attribute rating technique (SMART). Results revealed that the procurement/delivery system with the highest score, for all contractual packages, is the integrated project delivery method (IPD) under which other procurement/delivery methods could be utilized such as performance-based contracting (PBC), and construction management (CM). Further in this research, a sensitivity analysis approach was adopted to validate the IPD selection, and to determine the most critical criterion and the most critical measure of performance for each contractual package.